Kebutuhan Discharge Planning Pascaoperasi Pada Pasien Fraktur Ekstremitras Bawah - islami, asmi dinul; Rahayu, Urip; Aditya, Bambang (Jurnal Keperawatan 'Aisyiyah, 2019)
Post-surgery fracture patients have discharge planning needs that must be completed, among others are pain management, aids, nutrition, medication, wound treatment, and control time. Fracture patients are prone and have a high risk to infection, complication and length of hospitalization, so that post-surgery patients need comprehensive information related to discharge planning needs. This research is aimed to describe the need of discharge planning on patients with lower extremity fracture in Marjan Atas Room dr. Slamet Garut Hospital. The methodology used in this research is descriptive quantitative. The population of this research is the post-surgery patients with lower extremity fracture, the sample of this research is 30 respondents gained by using total sampling technique. The data of the research is gained with Instrument made by the researcher based on Potter & Perry theory. The instrument contains 28 questions with measurement scale: strongly needed and less needed. The research data was analyzed using frequency distribution based on question items at each sub variable. The results showed that most of the post-surgery discharge planning needs with the mostly need category is of 60% based on sub variables of nutrition, medication, mobilization, wound treatment, pain management, and aids. The sub variable that is less needed is control time. From the research above, it can be concluded that the need for post-surgery discharge planning for fracture is nutrition, medication, mobilization, treatment care, pain management, and aids. It is suggested that the patient need and be give nutrition officer, pharmacist or nurse to explain patient care at home using leaflet media.